2021
DOI: 10.3390/toxins13110773
|View full text |Cite
|
Sign up to set email alerts
|

Bee Venom Prevents Mucin 5AC Production through Inhibition of AKT and SPDEF Activation in Airway Epithelia Cells

Abstract: IL-13 induces mucus metaplasia, which causes airway obstruction in asthma. Bee venom (BV) and its components have shown anti-inflammatory effects in allergic diseases such as atopic dermatitis and asthma. In this study, we investigated the effect of BV on IL-13-induced mucus metaplasia through activation of the signal transducer and activator of transcription (STAT6), and regulation of SAM-pointed domain containing Ets-like factor (SPDEF) and forkhead box A2 (FOXA2) in the airway epithelia cell line A549. In A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…BV prevented forkhead box A2 (FOXA2)-regulating mucin 5AC (MUC5AC) expression in IL-13-treated A549 cells not only through inhibiting Akt activation but also by suppressing enhanced SAM-pointed domain containing Ets-like factor (SPDEF), which demonstrated that BV could help prevent mucus metaplasia in asthma ( Kim et al, 2021d ). Although iPSCs is considerable practical in potential cell-based therapy, they remain confronted with problems such as teratoma formation.…”
Section: Protect Effect On Other Diseasesmentioning
confidence: 99%
“…BV prevented forkhead box A2 (FOXA2)-regulating mucin 5AC (MUC5AC) expression in IL-13-treated A549 cells not only through inhibiting Akt activation but also by suppressing enhanced SAM-pointed domain containing Ets-like factor (SPDEF), which demonstrated that BV could help prevent mucus metaplasia in asthma ( Kim et al, 2021d ). Although iPSCs is considerable practical in potential cell-based therapy, they remain confronted with problems such as teratoma formation.…”
Section: Protect Effect On Other Diseasesmentioning
confidence: 99%